Hearing and sex: an analytical study - Bhat, Neeti; Mahotra, Narayan Bahadur; Shrestha, Lava; Tripathi, Prashant; Shrestha, Tirtha Man; Karna, Alina; Gupta, Mudit (Journal of Physiological Society of Nepal, 2021)
Background: Auditory differences among male and female is an underexplored topic. Sex-specific process of evolution has lead to differences in the physiology of male and female. For a long time, health equity has been confronted due to unawareness among health care providers that the findings are usually derived from research conducted among male. The objective of this study was to find differences in hearing threshold among healthy male and female. Materials and Methods:This was a hospital-based cross-sectional study conducted on age-matched male and female groups. Independent student’s t-test was used to compare hearing thresholds at different frequencies between males and females. Result:There were 23 males, and 23 age-matched females recruited in the study. The mean age of male participants was 52.65±14.41 years, and that of female participants was 51.41±11.34 years. The differences in hearing threshold were not statistically significant at 250 Hertz, 500 Hertz, 1000 Hz, 2000 Hz, 3000 Hz, 4000 Hz and 8000 Hz of both ears. However, a higher threshold was observed in females at most frequencies. Conclusion: Although the hearing threshold was higher among females, observed differences in the hearing threshold between males and females were not significant.